(Mis)Perceptions of Ethnic Group Size and Consequences for Community Expectations and Cooperation With Law Enforcement. (April 2018) - Miles-Johnson, Toby; Fay-Ramirez, Suzanna; Wiedlitzka, Susann
The changing composition of race and ethnic group size has been noted for Western nations over the last 15 years. Analysis of this change has linked fear of crime and attitudes toward immigrants and prejudice. Changes in ethnic composition are associated with movement of White residents out of traditionally White communities, rising ethnic tension as the ethnic mix shifts, and a heightened sense of injustice regarding the justice system. (Mis)perceptions of ethnic groups size shape attitudes toward minority groups, as well as policy, practice, and individual behavior in the context of the community. This study seeks to understand the extent of such misperceptions in the Australian context and whether misperceptions of race and ethnic composition are associated with beliefs and attitudes toward formal and informal social control. Utilizing Blalock's racial threat hypothesis, this study analyzes whether perceived relative ethnic group size is associated with self-reported willingness to cooperate with police as a way to minimize perceived threat. Findings suggest that respondents overestimate the size of minority populations while underestimating the majority White composition and that these misperceived distortions in ethnic group size have consequences for informal and formal social control.